Role-Playing Learning with a Disaster Mitigation Theme to Improve the Socialization Skills of Kindergarten Children - Putu Fanny Gayatri; Didith Pramunditya Ambara; Dewa Gede Firstia Wirabrata (Universitas Pendidikan Ganesha, 2026)
Low social skills in children lead to egocentric behavior, difficulty sharing and taking turns, and difficulty understanding peers' feelings. Several factors, including the lack of variation in engaging learning methods, influence this. This study aims to analyze the social abilities of Group B children in kindergarten through the implementation of the role-playing learning method. The study employed a classroom action research (CAR) design based on the Kemmis and McTaggart model, which comprises the stages of planning, action, observation, and reflection. The subjects of the study were six children in Group B at the kindergarten. The research was conducted in two cycles, each consisting of two meetings, with data collection techniques including observation and documentation. The results showed that, in Cycle I, children’s social skills increased from 24.95% to 37.45%, yet remained categorized as poor. In Cycle II, there was a significant improvement from 58.33% to 87.49%, categorized as very good. It can be concluded that the role-playing method is proven effective in improving the social skills of Group B children in kindergarten. The implementation of the role-playing method in early childhood has important implications for enhancing children’s social skills, empathy, and cooperation comprehensively.